A VISUAL BASIC PROGRAM FOR SERCHING FILES IN A CDSASTRONOMICAL CATALOGUES - Abood, Kamal; Ezzat, Ramy (Iraqi Journal of Science, 2024)
An algorithm was designed for searching a specify files within the astronomical catalogues, a program (in visual basic language) has been written to make a survey for an astronomical radio sources. This program gives the user a facility to access to any word on any text file in the catalogue.The program includes six searching cases, searching for any word, searching for frequency unit like (MHz), searching for specific values of frequency between minimum and maximum values, searching for declination words, searching for right ascension words, searching for journals, and Searching for authors.The data files for this program were loaded from website of CDS catalogue internet web site, 85 files for radio sources are loaded in our system as a first data collection to establish our system memory bank .This memory can be updated this data by adding more files to our system. A test for the program was carried out in all searching cases.